Justice and judgement the rise and the prospect of the judgment model in contemporary political philosophy - Ferrara, Alessandro (Philosophy & social criticism series, 1999)
Justice and Judgement is a comprehensive introduction to theories of judgement in contemporary political and moral philosophy. The book offers a critical examination of judgement in the recent works of Rawls, Habermas, Ackerman, Michelman and Dworkin, including an historical overview of the judgement model in contemporary political philosophy; the function of the constitution; and deliberative democracy. The book concludes with a discussion of universalism and contemporary liberalism and the judgement view of justice